PowerScope a Class II corrector - A case report - Joby Paulose; Palathottungal Joseph Antony; Brijesh Sureshkumar; Susha Mariam George; Manu Mundackal Mathew; Joseph Sebastian (Wolters Kluwer Medknow Publications, 2016)
Managing mild to moderate Class II malocclusion is a one of the common and major challenges to orthodontists. Class II discrepancies with mandibular deficiency during active growth are usually treated by myofunctional appliances. Fixed functional appliances evolved due to the noncompliance with conventional myofunctional appliances. This case report illustrates the efficiency of PowerScope in correction of skeletal Class II with mandibular deficiency in a patient aged 13 years who has reported to the department with a chief complaint of forwardly placed upper front teeth. This case with functional jaw retrusion was treated initially with MBT 0.022" prescription followed by PowerScope. Pre-, mid- and post-treatment cephalograms were obtained, and cephalometric analysis was performed. Stable and successful results were obtained with a substantial improvement in facial profile, skeletal jaw relationship, and overall esthetic appearance of the patient. A significant forward displacement of the mandible was the principal element for successful correction of Class II malocclusion. PowerScope provides the best results for Class II management, thus enables us to treat such cases by a nonextraction approach rather than contemplating extractions.